Management of chronic luxated central incisor with hopeless prognosis - Gauresh Kumar Patel; Sheela Kumar Gujjari; B M Annapoorna; S C Veerendra Kumar (Wolters Kluwer Medknow Publications, 2013)
Traumatic injuries are the most studied yet most challenging for a dentist. Extrusive luxation injuries are usually managed by repositioning tooth in the original position and pulp sensibility is evaluated at regular periodic intervals. However, when injuries are chronic, tooth is necrotic with compromised periodontal support, treatment is a challenge. Intentional replantation utilizing growth factors in fibrin rich network of platelet rich fibrin can be a treatment modality in such patients where other restorative modalities to establish function-esthetics rehabilitation is not possible.